A Comparative Study Between the Effects of Aprepitant and Ondansetron for the Prevention of Postoperative Nausea and Vomiting after Laparoscopic Cholecystectomy - Qadeer Ahmed Wajid, Samina Ashraf, Sabir Khan, Hana Khurshid, Kiran Riaz Khan, Taoseef Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Postoperative nausea and vomiting is one of the most typical side effects following surgery and anaesthesia (PONV). There has been a significant paradigm shift in the approach taken to prevent PONV. There have also been a few new medical treatments for the prevention and treatment of PONV. Clinical trials and meta-analyses show that aprepitant prevents PONV better than ondansetron. Objective: To compare the frequency of PONV after administration of Aprepitant vs Ondansetron in laparoscopic cholecystectomy Materials and Methods: The Jinnah Hospital in Lahore's Laparoscopic Operation Theater conducted this randomised control trial over the course of six months, from 15 April to 15 October 2019. Two groups of patients were randomly assigned. Ondansetron 8 mg was given orally to Group O two hours before induction with a sip of water. Two hours prior to induction, Group A took 80 mg of aprepitant orally with a sip of water. Every patient was instructed to fast for 6–8 hours. A 20G cannula was used to create an intravenous line after entering the operation room, and Ringer lactate was started. During surgery, the following parameters are all monitored: heart rate, oxygen saturation (SpO2), electrocardiography, noninvasive blood pressure (NIBP), and end-tidal carbon dioxide concentration (EtCO2). Using an intravenous infusion of propofol 2 mg/kg, anaesthesia was induced. Atracurium 0.6 mg/kg intravenous was used to aid in endotracheal intubation. In order to maintain anaesthesia, oxygen and (0.5–1%) isoflurane were used. As an analgesic, nalbuphine 0.1 mg/kg and paracetamol 15 mg/kg were administered. Neostigmine 0.04 mg/kg intravenous and Glycopyrotate 0.008 mg/kg intravenous were administered at the conclusion of operation to reverse the neuromuscular blockade. The last stitch or staple was made at 0 hours. Prior to surgery, the patient or attendant was instructed to contact the on-call doctor about any episodes of PONV. PONV occurrence was observed every 12 hours for 48 hours. Results: In this study we compared Aprepitant and Ondansetron on prophylaxis of PONV in patients undergoing laparoscopic cholecystectomy. Results showed that frequency of PONV was significantly higher with Ondansetron as compared to Aprepitant. i.e. (14.6% vs. 24.2%, p-value=0.032). From 0-12 hours frequency of PONV was higher with Ondansetron while from 12-24 hours PONV was higher in Aprepitant. Practical Implication: Government and hospitals should devise ways and procedures for effective research work for the benefit of patients, so that patient’s post-operative complications and symptoms can be managed efficiently. Conclusion: Aprepitant is more effective than ondansetron at preventing PONV in patients having laparoscopic cholecystectomy, according to the findings of this trial. Keywords: Vomiting, Postoperative nausea, PONV, Aprepitant, Cholecystectomy, Ondansetron, General anesthesia